Laparoscopic surgical treatment of gastroesophageal reflux disease combined with severe obesity - Oral Ospanov; Akzhunus Orekeshova (National Scientific Medical Center, 2016)
Aims: to compare antireflux and bariatric effect of fundoplication by Floppy-Nissen with fundoplication in combination with gastroplication. Methods. Laparoscopic Surgery for severe obesity combined with gastroesophageal reflux disease. A pilot randomized two-arm controlled clinical study was conducted by comparison of standard Nissen fundoplication (LFN) on one side and plication of greater gastric curvature combined with Nissen fundoplication on the other side (LFN+LGP). The study included 114 patients with gastroesophageal reflux disease with BMI of 30-39.9 kg/m2. The following indices were used for efficiency criteria: 24-hour pH measurement with calculation of DeMeesster index, percentage of excess body weight reduction, and patients' life quality evaluation, for which Bariatric analysis and reporting outcome system (BAROS) with Moorehead - Ardelt Quality of Life Questionnaire IIscoring key was used. Postoperative evaluation of life quality and dynamic of key GERD symptoms was conducted by GERD-HRQL questionnaire. Results. All operations were performed laparoscopically. Deaths and severe complications in both groups were not observed. The average time of hospital stay in both groups amounted to 4.291 ± 0.53 (P <0.0001). Antireflux function after surgery was without significant statistical differences. Bariatric effect was better in the first group (LFN + LGP) EWL72.99 ± 10.86, and EWL24.17 ± 8.8 (P <0.0001) in the second. A year after surgery BMI was 27.44 ± 1.56 in the first group, and 32.31 ± 1.95 (P <0.0001) in the second. Conclusions. The proposed laparoscopic surgical method is applicable for simultaneous treatment of obesity in conjunction with gastroesophageal reflux disease. Antireflux efficiency of the proposed restrictive gastroplication combined with fundoplication is identical to properties of standard Nissen fundoplication.